Temporalidades e contexto : tentativa de esgotamento de uma capa de Le Monde Diplomatique Brasil - Jullian Pereira Lopes de Oliveira (2021)
In this dissertation, the relations between temporality and the production of meanings on the covers of printed information media are investigated, based on contextualization processes. To this end, the covers of Le Monde Diplomatique Brasil are analyzed, whose verb-visual conformation tends to contrast with most of the printed media in circulation in the country. Published nationally for over 13 years on Brazilian soil, the monthly publication seems to operate on an unusual frontier: an informative media both Brazilian and foreign; a format that oscillates between newspaper and magazine; and an amalgamation of singular temporalities that give the journal its own time the reading and enjoying. Faced with this object, of complex contoured, this research turns to the temporal networks derived from the textual relations of this materiality, in order to understand how the cover, a communication device, regulates and mediates communicational exchanges through the confluence of non-linear times. For this, we use an analytical gesture inspired by the exercise of construction of meanings proposed by Georges Perec, in his book “An Attempt at Exhausting a Place in Paris” (1974). This movement seeks, from an errant and embedded gaze, to reveal the rigidity commonly imposed by journalistic conventions, which tend to impose stability in communicative relations, emptying their historical and contextual multiplicities. Therefore, we seek to explore the verb-visual texts on the covers, rejecting the idea of a textual immanentism, in order to find in the text's own instability its potential for the production of meanings.